Tribe-specific satellite DNA in non-domestic Bovidae - Kopecna, Olga; Kubickova, Svatava; Cernohorska, Halina; Cabelova, Katerina; Vahala, Jiri; Martinkova, Natalia; Rubes, Jiri (Chromosome research, 2014)
Satellite sequences present in the centromeric and pericentric regions of chromosomes represent useful source of information. Changes in satellite DNA composition may coincide with the speciation and serve as valuable markers of phylogenetic relationships. Here, we examined satellite DNA clones isolated by laser microdissection of centromeric regions of 38 bovid species and categorized them into three types. Sat I sequences from members of Bovini/Tragelaphini/Boselaphini are similar to the well-documented 1.715 sat I DNA family. Sat I DNA from Caprini/Alcelaphini/Hippotragini/Reduncini/Aepycerotini/Cephalophini/Antilopini/Neotragini/Oreotragini form the second group homologous to the common 1.714 sat I DNA. The analysis of sat II DNAs isolated in our study confirmed conservativeness of these sequences within Bovidae. Newly described centromeric clones from Madoqua kirkii and Strepsiceros strepsiceros were similar in length and repetitive tandem arrangement but showed no similarity to any other satellite DNA in the GenBank database. Phylogenetic analysis of sat I sequences isolated in our study from 38 bovid species enabled the description of relationships at the subfamily and tribal levels. The maximum likelihood and Bayesian inference analyses showed a basal position of sequences from Oreotragini in the subfamily Antilopinae. According to the Bayesian inference analysis based on the indels in a partitioned mixed model, Antilopinae satellite DNA split into two groups with those from Neotragini as a basal tribe, followed by a stepwise, successive branching of Cephalophini, Aepycerotini and Antilopini sequences. In the second group, Reduncini sequences were basal followed by Caprini, Alcelaphini and Hippotragini.
Keywords: Molecular Sequence Data; Sequence Analysis, DNA; Sequence Homology, Nucleic Acid; hybridizace in situ fluorescenční; repetitivní sekvence nukleových kyselin; genetická variace; Animals, Domestic; skot; DNA, Satellite; satelitní DNA; In Situ Hybridization, Fluorescence; Genetic Variation; Base Sequence; sekvence nukleotidů; hospodářská zvířata; zvířata; fylogeneze; Cattle; Species Specificity; sekvenční analýza DNA; sekvenční homologie nukleových kyselin; druhová specificita; molekulární sekvence - údaje; Phylogeny; Repetitive Sequences, Nucleic Acid; Animals